STRATEGI PENGEMBANGAN DESA WISATA TENUN IKAT TROSO DI JEPARA, JAWA TENGAH - Triyono, Joko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
This research aims to study the strengths and weaknesses and challenges to formulate strategies and development programs in Troso Ikat Weaving Tourism Village. This study uses a qualitative method. Data were collected by observation, in-depth interviews, documentation and distribution of questionnaires to 100 respondents, then analyzed using Strengths, Weakness, Opportunities and Threats (SWOT) Analysis. Based on the SWOT Analysis, the results of the study show that the number of male visitors is 64 people or 64%. Of the many visitors, most are anticipated between 41-50 years, which is 66 people or 66%. Visitors interested from different backgrounds, but participated in the profession as an entrepreneur with a total of 54 people or 54%. From this study also obtained results consisting of alternative strategies that can be applied to develop Troso Ikat Weaving Tourism Village, namely by creating diverse and quality products, making tour packages, combining with various parties, conducting promotional strategies using print and digital media, such as websites and social media. Keywords: Tourism Development, Swot Analysis, Product Innovation, Tourism Promotion